Toward a great and enduring profession. - Wing, Michael
SE is emerging from years of turmoil. Practitioners are beginning to stand up for themselves and their profession. I have seen them do so in Technology Review and heard them on NPR. Practitioners are fighting for their jobs, against outsourcers, like the SEI.
Keywords: Computing milieux; The Computing Profession; Occupations; Software; Software engineering; The Computer Society; Human factors